Bound on the Minimum Eigenvalue of H-Matrices Involving Hadamard Products. (19th June 2013) - Du, Kun; Gu, Guiding; Liu, Guo
Abstract : We present a new lower bound on the minimum eigenvalue of H -matrices involving Hadamard products τ ( A 1 ( α 1 ) ∘ ⋯ ∘ A m ( α m ) ), and we show that our lower bound is larger than the lower bound ∏ k = 1 m [ τ ( A k ) ] α k . Three examples verify our result.